Use of modeling for studying the growth of Tithonia diversifolia collection 17 - Ruiz, T.E.; Torres, Verena; Febles, Gustavo; Rodr?guez, H.; Gonz?lez, J. (Cuban Journal of Agricultural Science, 2012)
This study was conducted under dry conditions to describe the performance of some morphological components of the collection 17 of Tithonia diversifolia, through the use of different statistical criteria and to determine the models of best goodness of fit. The indicators were determined every two weeks for 16 weeks. In two moments of 2006 and 2007, from June to October and from January to June respectively, a sampling for each climatic season was conducted: seedling height (cm), weight of 100 leaves green matter (g) (weight 100 L GM), weight of the integral plant green matter (g) (weight IP GM), total weight of a linear meter (g) and green matter (total weight 1 m GM). The variables expressed in DM did not have proper goodness of fit with the models used. The Richards model was not adequate for describing the performance of the variables studied. In the rainy season, the seedling height was adjusted to a logistic model, while the weight of 100 leaves GM had a quadratic performance and that of IP GM was exponential. The weight of 1 m GM did not have significant adjustment for the models considered. The seedling height reached a little bit more than 200 cm in week 18, with a fortnightly growth rate of 0.21 cm. the weight of 100 leaves GM achieved the maximum increase at week 12. The diminishing of the leaves weight was rapid from this time on. The weight of the integral plant showed a tendency to keep increasing after week 18, with value of 87.41 in the last week. During the dry season, the linear model explained the seedling height, and the quadratic that of 100 leaves GM. The exponential referred the IP of the plant GM, and the total weight 1 m GM. The linear dynamics of the seedling height explained an increase of 3.0 cm weekly and 62 cm, as superior height at 18 weeks. The weight of 100 leaves and that of the integral plant reached very low values up to week 18, when both variables increased rapidly, reaching higher values of almost 250 and 100 g. It is concluded that Tithonia diversifolia plant material 17 had the best growth characteristics during the rainy season between weeks 12 and 14, including the last. In the dry season, its best growth was from week 12 on. The information allows further studies based on biomass production, even for cutting or grazing, when knowing the performance of different plant components in time. Key words: growth, modeling, Tithonia diversifolia